Regional variation in suicide rates in Sri Lanka between 1955 and 2011: a spatial and temporal analysis - Knipe, D.W.; Padmanathan, P.; Muthuwatta, Lal P. (Springer, 2017)
Background: Between 1955 and 2011 there were marked fluctuations in suicide rates in Sri Lanka; incidence increased six-fold between 1955 and the 1980s, and halved in the early 21st century. Changes in access to highly toxic pesticides are thought to have influenced this pattern. This study investigates variation in suicide rates across Sri Lanka’s 25 districts between 1955 and 2011. We hypothesised that changes in the incidence of suicide would be most marked in rural areas due to the variation in availability of highly toxic pesticides in these locations during this time period. Methods: We mapped district-level suicide rates in 1955, 1972, 1980 and 2011. These periods preceded, included and postdated the rapid rise in Sri Lanka’s suicide rates. We investigated the associations between district-level variations in suicide rates and census-derived measures of rurality (population density), unemployment, migration and ethnicity using Spearman’s rank correlation and negative binomial models. Results: The rise and fall in suicide rates was concentrated in more rural areas. In 1980, when suicide rates were at their highest, population density was inversely associated with area variation in suicide rates (r = -0.65; p < 0.001), i.e. incidence was highest in rural areas. In contrast the association was weakest in 1950, prior to the rise in pesticide suicides (r = -0.10; p = 0.697). There was no strong evidence that levels of migration or ethnicity were associated with area variations in suicide rates. The relative rates of suicide in the most rural compared to the most urban districts before (1955), during (1980) and after (2011) the rise in highly toxic pesticide availability were 1.1 (95% CI 0.5 to 2.4), 3.7 (2.0 to 6.9) and 2.1 (1.6 to 2.7) respectively. Conclusions: The findings provide some support for the hypothesis that changes in access to pesticides contributed to the marked fluctuations in Sri Lanka’s suicide rate, but the impact of other factors cannot be ruled out.